Ответы
![](/img/user_avatar.png)
X^2 + y^2 +2x +4y +1 =0
(x^2 + 2x + 1) - 1 + (y^2 +4y + 4) -4 +1 =0
(x+1)^2 + (y+2)^2 -4 =0
(x+1)^2 + (y+2)^2 = 4
(x+1)^2 + (y+2)^2 = 2^2 - уравнение окружности с цетром в точке (-1, -2) и радиусом 2
![X^2 + y^2 +2x +4y +1 =0<br>(x^2 + 2x + 1) - 1 + (y^2 +4y + 4 X^2 + y^2 +2x +4y +1 =0<br>(x^2 + 2x + 1) - 1 + (y^2 +4y + 4](https://ru-static.z-dn.net/files/dc9/c53ca336b02039d20c9c3a64e6275e8d.jpg)
Нет комментариев
Похожие вопросы
Математика
Упростите выражение (х-39)+65 скажите пж...
Математика
Решите уравнения 948 - с : 3 = 586...
Математика
15732:57:(156:13) столбиком плиз...